Benzylation of benzene and other aromatics by benzyl chloride over mesoporous AlSBA-15 catalysts - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hartmann, Martin; Halligudi, Shivappa B. (Microporous and Mesoporous Materials, 2005)
Aluminum-containing mesoporous molecular sieves AISBA-15 with different n(Si)/n(Al), ratios and AIMCM-41 have been synthesized hydrothermally and characterized in detail by physicochemical methods, viz. XRD, N(2) adsorption and (27)Al NMR spectroscopy. The low angle XRD and N2 adsorption measurements reveal that the structural order of SBA-15 was retained after the incorporation of Al. The increase of the unit cell parameter with increasing aluminum content and (27)Al MAS NMR spectroscopy confirm the incorporation of aluminum in the framework. Benzylation of benzene and substituted benzenes reaction employing benzyl chloride as the alkylating agent over AISBA-15 and AIMCM-41 have been investigated. The influence of various reaction parameters such as reaction temperature, reactant feed ratio and catalyst amount affecting the activity and selectivity of AISBA-15, have been studied. Among the mesoporous catalysts studied, AISBA-15(45), where the number in parentheses indicates the molar nsilnA, ratio, shows both high conversion and high selectivity for the benzylation of benzene. The activity of this catalyst for the benzylation of different aromatic compounds is in the following order: benzene > toluene > p-xylene > mesitylene > anisole. Kinetics of the benzene benzylation over different catalysts have also been investigated. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Alkylation; AlSBA-15; Benzylation; SBA-15

Direct synthesis of well-ordered and unusually reactive FeSBA-15 mesoporous molecular sieves - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hossain, K. Z.; Halligudi, Shivappa B.; Hartmann, Martin; Nomura, M. (Chemistry of Materials, 2005)
Large-pore hexagonal SBA-15 molecular sieves partially substituted with iron(III) have been synthesized for the first time in highly acidic media. The degree of iron(III) incorporation into SBA-15 can easily be controlled by a simple adjustment of the molar ratio of water and hydrochloric acid. All the materials have been characterized by XRD, N-2 adsorption, UV-Vis DRS, ESR, and XANES spectroscopy. The characterization of the FeSBA-15 materials by UV-Vis DRS, ESR, and XANES spectroscopies suggests that the iron atoms are highly dispersed and mostly occupy isolated tetrahedral sites. XANES studies revealed that the proportion of tetrahedrally coordinated Fe atoms decreases with decreasing n(Si)/n(Fc) ratios. Benzylation of benzene (or substituted benzenes) using benzyl chloride as the alkylating agent over FeSBA-15 with different n(Si)/n(Fe) ratios was investigated as was the same reaction using AISBA-15 as catalyst. The influence of parameters such as reaction temperature, reactant feed ratio, and the presence of electron-donating substituents on the activity and selectivity of AISBA-15 was studied. Under optimized reaction conditions, the FeSBA-15 catalyst showed a superior catalytic performance in the benzylation of benzene and other aromatics using benzyl chloride, with a clean conversion of benzyl chloride to the monoalkylated product (100% selectivity) with a very high rate constant when compared to other mesoporous materials such as AISBA-15 and FeHMS. Interestingly, use of FeSBA-15(21) resulted in quantitative conversion of benzyl chloride with a high rate constant of 2420.5 x 10(-4) min(-1) under the optimized reaction conditions.

Highly active and selective AlSBA-15 catalysts for the vapor phase tert-butylation of phenol - Vinu, A.; Devassy, Biju M.; Halligudi, Shivaraj B.; Bohlmann, W.; Hartmann, Martin (Applied Catalysis A-General, 2005)
Hexagonally ordered mesoporous AISBA-15 catalysts having n(Si)/(nA]) ratios from 7 to 215 have been synthesized hydrothermally using a cheap non-ionic block copolymer as the structure-directing agent. The obtained materials were analyzed by XRD and nitrogen adsorption to determine the structural order and the textural properties. It has been observed by Al-27 MAS NMR spectroscopy that aluminum atoms are exclusively in tetrahedral coordination for all samples except AISBA-15(7), where octahedral aluminum has been detected to some extent. Temperature-programmed desorption of pyridine showed that AISBA-15(45) has a higher number of strong acid sites as compared to other mesoporous materials such as FeMCM-41, AIMCM-41 and FcAlMCM-41. The catalyst AlSBA-15(45)showed superior performance in the acid-catalyzed tertiary butylation of phenol employing tert-butanol as the alkylation agent. A high phenol conversion of 86.3% is observed for this catalyst at a reaction temperature of 150 degrees C. Over AISBA-15(45), the 4-TBP yield amounts to 40.5% and the 2,4-DTBP yield corresponds to 37.9%. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Acidity; AlSBA-15; aluminum incorporation; butylation of phenol; SBA-15

Effect of pretreatment conditions on the catalytic activity of nano-sized TPA/ZrO2 dispersed in SBA-15 channels in acetylation reactions - Sawant, Dhanashri P.; Hartmann, Martin; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2007)
Acetylation of an aromatic compounds such as veratrole (1,2-dimethoxybenzene), anisole, thioanisole, isobutyl benzene and 2-methoxynaphthalene with acetic anhydride has been investigated over a nano-sized 12-tungstophosphoric acid (TPA)/22.4 wt.%ZrO2/SBA- 15 catalysts in the liquid phase conditions. Catalysts with different (%) TPA and zirconia loadings calcined at different temperatures were prepared by wet-impregnation and characterized by XRD, N-2 adsorption-desorption, FT-Rarnan, X-ray photoelectron spectroscopy (XPS). The acidic behavior of the catalyst was studied by TPD of ammonia and FT-IR pyridine adsorption. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/SBA- 15 calcined at 1123 K had the highest acidity and was the most active catalyst in veratrole acetylation with acetic anhydride. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: acetylation; SBA-15; TPA/ZrO2; veratrole; wet-impregnation

Electrostatic grafting of a triphenylphosphine sulfonate on SBA-15: application in palladium catalyzed hydrogenation - Wang, Lei; Dehe, Daniel; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Zhou, Zhou; Hartmann, Martin; Taylor, Robin N. Klupp; Singh, Anand Pal; Jia, Mingjun; Thiel, Werner R. (Catalysis Science & Technology, 2012)
A novel strategy for the immobilization of a sulfonate functionalized triphenylphosphine ligand by ion-ion interactions on an imidazolium modified SBA-15 is presented. A support containing electrostatically grafted triphenylphosphine as the ligand was reacted with PdCl2( CNPh)(2) and the resulting hybrid material catalyzed olefin hydrogenation under mild conditions. The catalyst exhibits excellent activity, selectivity and stability and it can be reused for at least ten times without any loss of activity. An analogous but covalently grafted palladium system does not show any hydrogenation activity under the same conditions. TEM images of the used catalyst clearly prove the absence of palladium nanoparticles. Additionally, XPS investigations prove that palladium( 0) is formed and the phosphine is oxidized. By AAS no palladium contamination down to 0.5 X 10(-4) mmol could be detected in the products and further leaching tests verified the reaction to be truly heterogeneous. This concept of non-covalent immobilization guarantees a tight bonding of the catalytically active species to the surface in combination with a high mobility, which should be favorable for other catalyses, too.